The seven deadly sins of white Christian nationalism: a call to action - Heyward, Carter (Religion in the Modern World Series, 2022)
As right-wing conservatives dare to call themselves Christians while tearing down equality and justice and fanning the flames of fascism in America, Carter Heyward issues a call to action for true lovers of God. Only by condemning the destructive culture of white Christian nationalism can we fashion a world full of God's truth, love, and wisdom.